Student Beliefs About the Learning Task in Physics - Dickie, Leslie O.; Kato, Carolyn K. (Canadian Journal of Higher Education, 1996)
In an investigation of students' perceptions and experiences of learning physics open-ended interviews were undertaken with nine students in a university honors mechanics course. A thematic analysis of the interview transcripts showed that the students saw themselves learning primarily outside of the classroom as they solved the problems that made up the assignments. Students reported that they had been introduced to Newton's laws in high school and few new concepts were now being introduced. They saw themselves as having moved beyond the memorization of content to the use of this content in solving more realistic problems and in relating the solutions to their prior experience. Students' approaches to the learning task were also influenced by their interactions with classmates and friends and by their perceptions of the actions of the professor in the classroom. However the perceptions of the students were at times at odds with the intentions of the professor who saw the nature of physics as a major influence on his approaches and actions. Unless both teacher and student are prepared to come to a shared understanding of the learning task, misconceptions about both physics and the learning of physics will continue to impede learning.